An Impactful Story of Education Empowerment and Lifelong Learning Coaching in Jeruk Purut Village - Growing Minds, Changing Lives: Kisah Pemberdayaan Pendidikan dan Pembinaan Pembelajaran Sepanjang Hayat di Desa Jeruk Purut yang Berdampak—Menumbuhkan Pikiran, Mengubah Kehidupan - Putri, Devi Widyas; Laili, Nurfi; Rohmatunnadjila; Amalia , Rahma (Proceedings of The ICECRS, 2023)
The aim of this service is to increase access to education to encourage lifelong learning, everyone in Jeruk Purut Village, including children, teenagers and adults, must receive a better education. The service method carried out is preparing an educational program to meet the needs and potential of Jeruk Purut Village, designing an educational program that includes formal and non-formal education. The results of this service can improve community skills and increase the skills and knowledge of the people of Jeruk Purut Village in various fields through a lifelong learning program. The implications resulting from this service are community empowerment, increasing the role and participation of the community in building and maintaining a sustainable education system. It is hoped that the history of educational empowerment and lifelong learning training in Jeruk Purut Village will improve the quality of life and development opportunities Highlights: Holistic Educational Program: Designing a comprehensive educational program that caters to the diverse needs and potentials of Jeruk Purut Village, encompassing both formal and non-formal education. Community Involvement and Participation: Fostering increased engagement of all age groups, including children, teenagers, and adults, to enhance community skills and knowledge, promoting a culture of lifelong learning. Empowering Sustainable Development: The service aims to empower the community, contributing to the establishment and maintenance of a sustainable education system, thereby improving the overall quality of life and developmental opportunities in Jeruk Purut Village. Keywords : Lifelong Learning, Transformative Education, Educational Empowerment